Rozhodování rodičů o odkladu školní docházky v kontextu výběru školy - Kristýna Vlčková (Orbis Scholae, 2018)
Delays in commencing school attendance are frequent in the Czech Republic, compared to the surrounding countries. According to Czech legislation, parents can opt for such a postponement and they can also decide which school the child enters. The purpose of this paper is to answer the question of how parents think about delaying the commencement of their children’s schooling in the context of primary school choice. In this study, I present the results of research in which I analyzed data obtained through ten in-depth interviews with parents of preschool children whose children attend a nursery school in the centre of a large city or parents planning to enrol their child in the first grade of primary school. These interviews focused on the topic of school choice and the subject of delayed commencement of school attendance emerged. The analysis of the interviews shows that parents choose a school in two ways. One is a strategy of an acceptable option by choosing the first acceptable primary school, while parents with a wish list strategy choose the best school from those that are available according to their own criteria. I show that these strategies can be preceded by the exclusion method, which means declining a local school, but this is only a zero step followed by one of the two school choice strategies. In conclusion, I state that the parents using the strategy of an acceptable option express greater confidence in the expertise of the institutions, and in their decisions about delayed commencement of school attendance they tend more to their own opinion than do parents with a wish list strategy. Parents with a wish list strategy are more independent in their decision making.